Corporate Social Responsibility Di Sektor Pertambangan Indonesia Tahun 2020 - Shovia Krismelina; Syaffina Aulya; Alifandy S. Mulawarman; M. Rakha Bhagaskara; Adliana Dwi Ramadhanti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The Covid-19 pandemic is ongoing in various parts of the world, starting from the city of Wuhan, China until the end of December 2019. This infection causes respiratory problems for its victims. This pandemic began to enter Indonesia in March 2020 which had an impact on various perspectives, especially the development of the Indonesian economy in various modern regions. This incident caused the organization to experience concerns about managing its business, one of which was the organization's anxiety about monetary reports due to the economic easing due to the pandemic. Reports on the CSR implementation process, however, in addition to presenting a wider local area of organizational profile and systems as well as the administrative approach taken as well as various financial benefits. profit. The purpose of this study is to find out the changes that occur in CSR reports during the 2020 pandemic by comparing the 2019 reports. The results of the research on annual reports and financial reports which state companies that do not report CSR. In 2019, there were 49 mining sector companies listed on the Indonesia Stock Exchange that did not report the results of their CSR reports, while in 2020 there were 47 mining sector companies listed on the Indonesia Stock Exchange with 5 companies that did not report CSR. In 2020 caused by covid-19 where the crisis conditions experienced by the mining sector have an impact on the issuance of CSR reports from companies where the company focuses on the main things being done or by reducing CSR costs so that the financial reporting process reaches the target.